Updating the description of Rhizobium diversity associated with common bean cultivars in the Ecuadorian Andes: A phylogenetic and functional perspective - Andrea León–Cadena; Henry D. Naranjo; Janine Jiménez–Parra; José Ochoa; Michelle Avalos–Loayza; Pamela Murillo; Angel Murillo; Gustavo Bernal; Juan Cadena–Villota; Lenin Ron-Garrido (PLoS ONE, 2026)
Phaseolus vulgaris (common bean) is nodulated by diverse Rhizobium species. Although Ecuador is recognized as one of the centers of bean diversification, its native rhizobial diversity and geographic distribution remains poorly characterized. We isolated 46 native Rhizobium strains from root nodules across four Andean provinces (Imbabura, Pichincha, Chimborazo, and Loja). Partial sequencing of the recA gene delineated nine strain clusters (R1–R9) within two major phylogenetic groups: (i) Rhizobium ecuadorense/Rhizobium leguminosarum/Rhizobium etli/Rhizobium phaseoli and (ii) R. tropici . Multilocus sequence analysis (MLSA) of the housekeeping genes recA , glnII , dnaK genes from 19 representative isolates showed four phylogenetic clusters (C1–C4). Cluster C1 ( R. ecuadorense –related) predominated in northern Ecuador; C2 formed a distinct Chimborazo cluster; C3 appeared sporadically in Imbabura and Chimborazo; and C4 ( R. tropici –related) was confined to Loja’s Amotape–Huancabamba Zone and displayed unique phenotypes. In greenhouse assays on two local bean varieties, all isolates formed nodules in both varieties; several isolates induced significantly higher nodule counts than the commercial inoculant UMR1899 ( Rhizobium tropici IIB CIAT 899 T ). These results suggest geographic variation among Ecuadorian Rhizobium populations and identify locally predominant groups for further evaluation as bioinoculants.